Dissipation and Adsorption Behavior Together with Antioxidant Activity of Pinocembrin Dihydrochalcone - Magdalena Dziągwa-Becker; Marta Oleszek; Aleksandra Ukalska-Jaruga; Mariusz Kucharski; Weronika Kozłowska; Marcel Białas; Sylwia Zielińska (Applied Sciences, 2025)
The excessive use of synthetic pesticides has not only resulted in increased resistance among weeds and pests, leading to significant economic loss, but has also raised serious health and environmental concerns. Chalcones and their derivatives, known for their herbicidal, fungicidal, bactericidal, and antiviral properties, are emerging as promising bio-based candidates. These naturally occurring compounds have long been recognized for their beneficial health effects and wide-range applications. However, their limited concentration in plants, along with poor solubility and bioavailability, brings challenges for their development. The aim of this study was to examine the properties of a synthetic substance, pinocembrin dihydrochalcone (3-phenyl-1-(2,4,6-trihydroxyphenyl)-1-propanone), including its soil dissipation and adsorption. Additionally, we evaluated its antioxidant activity through the DPPH assay and FRAP experiments. This analysis aims to provide insights into its potential classification as a low risk pesticide.